2004
DOI: 10.1007/s00204-003-0506-3
|View full text |Cite
|
Sign up to set email alerts
|

Vanadyl sulfate can differentially damage DNA in human lymphocytes and HeLa cells

Abstract: Using the comet assay, we showed that vanadyl sulfate induced DNA damage in human normal lymphocytes and in HeLa cells. Vanadyl at 0.5 and 1 mM produced DNA single- and double-strand breaks (SSBs and DSBs) in lymphocytes, whereas in HeLa cells we observed only SSBs. Post-treatment of vanadyl-damaged DNA from lymphocytes with formamidopyrimidine-DNA glycosylase (Fpg), an enzyme recognizing oxidized purines, gave rise to a significant increase in the extent of DNA damage. A similar effect was observed in HeLa ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 43 publications
(47 reference statements)
2
38
0
Order By: Relevance
“…Vanadyl compounds are reported to cause DNA lesions by hydrogen peroxide (H 2 O 2 ) formed by dismutation of superoxide anion radicals 8) and in long term can become genotoxic. 9) However, limited information is available about the reproductive toxicity of Vanadyl sulphate.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadyl compounds are reported to cause DNA lesions by hydrogen peroxide (H 2 O 2 ) formed by dismutation of superoxide anion radicals 8) and in long term can become genotoxic. 9) However, limited information is available about the reproductive toxicity of Vanadyl sulphate.…”
Section: Introductionmentioning
confidence: 99%
“…7,8) Vanadium compounds exert contractile effects on vascular and non-vascular smooth muscle, such as the guinea pig taenia coli, trachea, and gallbladder smooth muscle.9-11) The contractile effects of vanadates have been considered to be due to inhibition of PTPase, 9,11,12) but not ATPase, 13,14) because genistein, a protein tyrosine kinase inhibitor, attenuates vanadateinduced constriction. Vanadate-induced muscle constriction was regulated by activation of Rho kinase-dependent signaling in ileal longitudinal smooth muscle in guinea pigs, resulting in increased phosphorylation of the myosin light chain (MLC).…”
mentioning
confidence: 99%
“…7,8) Vanadium compounds exert contractile effects on vascular and non-vascular smooth muscle, such as the guinea pig taenia coli, trachea, and gallbladder smooth muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…* P \ 0.05; ** P \ 0.01; *** P \ 0.001 cytotoxicity of different chemicals (Drozdz et al 2011;Foldbjerg et al 2011;Klarić et al 2010;Viau et al 2009;Wozniak and Blasiak 2004). The tests performed on cell cultures and/or in the animal model indicated that agrochemicals could significantly increase DNA damage.…”
Section: Discussionmentioning
confidence: 99%